PENGENALAN PENTINGNYA DAN MANFAAT STANDAR OPERASIONAL PROSEDUR BAGI USAHA MIKRO KECIL MENENGAH MAKANAN RINGAN SECARA ONLINE - Abdul Haris Subarjo; Dedet Hermawan S.; Fajar Nugroho; Sudarmanto Sudarmanto; Sri Mulyani; Gunawan Gunawan (LPPM Universitas PGRI Adi Buana Surabaya, 2023)
Community service activities were attended by 29 participants from 33 registrants via Google form, this activity was carried out online using Google Meet. The purpose of this activity is to increase participants' knowledge about the importance and benefits of the stages in preparing standard operating procedures for their business. Another objective is to increase knowledge about the implementation of good standard operating procedures. Community Service activities are carried out through 3 stages consisting of: the preparation stage, the implementation stage, which consists of several phases, namely: the initial phase, the working phase (the servant introduces the activity participants, the servant conducts material presentation). The next stage is the activity evaluation stage which consists of evaluating the activity process and evaluating the results of the activity. The objective of community service activities has increased with an average increase of 47.84%. This shows that the knowledge of participants in community service activities regarding standard operating procedures has increased and is in accordance with the objectives of the activity.